Research on the Differences between the Securities Markets of China and the United States - Deng, Zeyu (Transactions on Economics, Business and Management Research, 2024)
This article aims to analyze the current development status and differences of the securities and fund industries in China and the United States and explore the reasons for the Chinese government’s reduced attention to securitization. The article first emphasizes the importance of securities funds in modern financial markets, pointing out the leading position of US mutual funds in the global mutual fund industry, as well as the rapid development of Chinese securities funds in recent years. The article reviews the current research status related to securitization, pointing out the development of securitization markets in China and the United States, as well as the importance of securitization in disposing of non-performing assets and complying with Chinese government policies. At the same time, the article also summarizes the legal deficiencies of the Chinese government in taxation, credit rating, and enhancement issues, and suggests improving the transparency of relevant securities information and establishing a unified trading execution system. When comparing the development of the fund industry between China and the United States, the article found that there are differences and similarities in investment strategies, government roles, and financial regulatory agency functions between the two countries. The article also explores the differences in the size, investor structure, and valuation levels of the securities markets in the United States and China, and analyzes the main reasons for market development history, regulatory system and legal environment, and market participant structure.